Assessment of prevalence of recurrent aphthous stomatitis in the North Indian population: A cross-sectional study - Ramneet Kaur; Ashima Bali Behl; Ramandeep Singh Punia; Kumar Nirav; Khundongbam Bikramjit Singh; Sukhpreet Kaur (Wolters Kluwer Medknow Publications, 2021)
Aim and Objective: The present study was undertaken for assessing the prevalence of recurrent aphthous stomatitis (RAS) in the North Indian population. Materials and Methods: Assessment of a total of 4255 patients was done over a period of 2 years, who came for a routine dental checkup. Recording of the complete demographic and clinical details of all the patients was done. The prevalence of RAS was assessed. Profile of patients with RAS was assessed separately. A pro forma was made and the type of treatment protocol followed by patients with RAS was also recorded. All the results were recorded in a Microsoft Excel sheet and were analyzed using SPSS software. Results: Analysis of a total of 4255 patients was done. RAS was found to be present in 800 patients. The overall prevalence of RAS was found to be 18.93%. Significant results were obtained when analyzing age, gender, and occupation as risk factors for RAS. Labial/buccal mucosa involvement occurred in 51.875% of the cases. In 44% of the cases, the size of the RAS was between 1 cm and 3 cm. Home remedy was followed in 17.875% of the cases. Conclusion: A significant proportion of patients in the North Indian population is affected by RAS. In comparison to males, females are more commonly affected.